2017
DOI: 10.1080/19420862.2017.1387346
|View full text |Cite
|
Sign up to set email alerts
|

Variability of intended copies for etanercept (Enbrel®): Data on multiple batches of seven products

Abstract: Fusion protein and monoclonal antibody-based tumor necrosis factor (TNF) inhibitors represent established treatment options for a range of inflammatory diseases. Regulatory authorities have outlined the structural characterization and clinical assessments necessary to establish biosimilarity of a new biotherapeutic product with the innovator biologic drug. Biologic products that would not meet the minimum World Health Organization's standard for evaluation of similar biotherapeutic products are available in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 30 publications
0
16
0
1
Order By: Relevance
“…Due to the proximity with Iran, these products may be accessible to some Iraqi patients. According to an analytical assessment of Altebrel, several attributes were not comparable to those of the originator: peptide sequence, distribution of charged species, and posttranslational modifications 52. Although the clinical impact of these differences is unknown, Altebrel should not be considered an etanercept biosimilar, and patients should not be switched between the two products.…”
Section: Methodsmentioning
confidence: 99%
“…Due to the proximity with Iran, these products may be accessible to some Iraqi patients. According to an analytical assessment of Altebrel, several attributes were not comparable to those of the originator: peptide sequence, distribution of charged species, and posttranslational modifications 52. Although the clinical impact of these differences is unknown, Altebrel should not be considered an etanercept biosimilar, and patients should not be switched between the two products.…”
Section: Methodsmentioning
confidence: 99%
“…60 Furthermore, a recent analytical assessment of seven intended copies of etanercept (among them Etanar® and Infinitam®) found that, although each copy exhibited a degree of similarity to the originator in structure and binding activity, a number of significant structural and biochemical differences were apparent. 61 None of the seven products met release-specification criteria typically applied to originator etanercept across all test assays. The study’s authors noted that the potential for unanticipated clinical consequences resulting from such differences should not be overlooked.…”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 96%
“…The study’s authors noted that the potential for unanticipated clinical consequences resulting from such differences should not be overlooked. 61 …”
Section: Biosimilars In Latin America: Current Situationmentioning
confidence: 99%
“…Cette approche également connue sous le nom de cartographie peptidique a aujourd'hui presque totalement remplacé les méthodes anciennes de séquençage des protéines, longues, fastidieuses et coûteuses, comme la dégradation d'Edman. Ainsi, des cartes peptidiques ont été réalisées pour deux AcM ou une protéine de fusion de référence et leurs biosimilaires (rituximab [12,13], adalimumab [14] et étanercept [15]). Dans ces études de comparabilité, la séquence d'acides aminés a été validée pour les biosimilaires du rituximab et de l'adalimumab, avec une couverture de séquence très proche ou égale à 100 %.…”
Section: La Structure Primaire De L'acm Biosimilaireunclassified